2017
DOI: 10.4274/turkderm.22804
|View full text |Cite
|
Sign up to set email alerts
|

Joint diagnosis of pediatric and dermatology clinics: Prospective observation of thirtynine patients with hand, foot and mouth disease

Abstract: Background and Design: Hand, foot and mouth disease (HFMD) is a childhood enteroviral eruptive disease presenting with fever and cutaneous and mucosal lesions. It is benign and generally resolves spontaneously, but may sometimes result in systemic involvement. The purpose of this study was to share our clinical experience concerning patients who were followed with the diagnosis of HFMD established by the pediatric and dermatology clinics. Materials and Methods: We prospectively evaluated patients who attended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…In our study , there was slight male predominance (boys: girls = 1.2 : 1) which was in accordance with Bucak et al and Ghosh et al 5,6 The predominant age group affected was 5.3 years in our study which was almost similar to Bucak et al (4.9 years) and Ghosh et al (5.1 years). 5,6 But, Li et al and Jeelani et al reported in younger age group of 3.5 years and 2.2 years respectively. 7,8 Nevertheless, our study is in accordance with literatures that HFMD is common around children of 5 years.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study , there was slight male predominance (boys: girls = 1.2 : 1) which was in accordance with Bucak et al and Ghosh et al 5,6 The predominant age group affected was 5.3 years in our study which was almost similar to Bucak et al (4.9 years) and Ghosh et al (5.1 years). 5,6 But, Li et al and Jeelani et al reported in younger age group of 3.5 years and 2.2 years respectively. 7,8 Nevertheless, our study is in accordance with literatures that HFMD is common around children of 5 years.…”
Section: Discussionsupporting
confidence: 91%
“…9 In our study, the vesicular lesions predominantly involved palms and soles in accordance with previous studies. 5,6 The second commonest site involved was oral cavity in our study similar to Bucak et al while Ghosh et al reported it as gluteal region. Atypical lesions of HFMD like lesions involving only one body region, lesions in trunk without palms, soles and oral involvement, involvement of genitalia has also been reported.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, it was determined that 40.4% of the children in the experimental group had fever, while none of the children in the control group had fever. In four different studies conducted in our country, the reported incidence of fever in children with hand-foot-and-mouth disease varied between 61.40% and 82.10% (6,(9)(10)(11). The incidence of fever was lower in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…In three different studies conducted in our country, the percentage of cases in children under the age of five was reported as 52.30%, 79% and 87.40%, respectively (6,9,10). In their study, Bucak et al reported the percentage of patients under the age of five as 92.30% and the percentage of patients under the age of one as 15.30% (11). It is stated that the younger the child, the greater the severity of the disease (7,12).…”
Section: Discussionmentioning
confidence: 88%